Synthesis of Imidazo[1,2‑a]pyridines: “Water-Mediated” Hydroamination and Silver-Catalyzed Aminooxygenation - Chandra Mohan, Darapaneni; Nageswara Rao, Sadu; Adimurthy, Subbarayappa (Journal of organic chemistry, 2013)
Aqueous syntheses of methylimidazo[1,2-a]pyridines without any deliberate addition of catalyst are reported. Imidazo[1,2-a]pyrazine and imidazo[2,1-a]isoquinoline were also obtained in good yields under similar conditions. With acetonitrile as solvent, Ag-catalyzed intramolecular aminooxygenation produced imidazo[1,2-a]pyridine-3-carbaldehydes in moderate to good yields.